(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
This article analyzes the reflection of the social sciences on the subject of migration, focusing the different forms of coexistence between natives and migrants. After examining the various configurations of public space, the author proposes a reflection on the concept of people as a jusgenerative dimension, open and discutable, marked by the interaction between majority cultures and minority cultural identities. In light of the potentiality of deliberative democracy and the distinction between moral and political consensus, the article examines some specific cases related to the presence of Islam in Europe. The affaire du foulard and the arranged marriage are thus read from the perspective of gender studies, which propose a critical and ambivalent interpretation of it.